2013
DOI: 10.1001/jamapsychiatry.2013.2174
|View full text |Cite
|
Sign up to set email alerts
|

Attention Network Hypoconnectivity With Default and Affective Network Hyperconnectivity in Adults Diagnosed With Attention-Deficit/Hyperactivity Disorder in Childhood

Abstract: The neurobiological underpinnings of attention-deficit/hyperactivity disorder (ADHD) and particularly those associated with the persistence of ADHD into adulthood are not yet well understood. The correlation patterns in spontaneous neural fluctuations at rest are known as resting-state functional connectivity (RSFC) and could characterize ADHD-specific connectivity changes. OBJECTIVE To determine the specific location of possible ADHD-related differences in RSFC between adults diagnosed as having ADHD in child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
96
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(116 citation statements)
references
References 50 publications
10
96
6
Order By: Relevance
“…Functional deficits of the ventral attentional network (including the supramarginal and angular gyri) are well known in ADHD (Helenius et al, 2011;Cortese et al, 2012;McCarthy et al, 2013;McLeod et al, 2014) and right-ward hyperactivation of the angular gyrus (Cortese et al, 2012) and a left-ward hypoactivation of the ventral attention system (McCarthy et al, 2013) were previously observed in ADHD adults and could be in line with our connectivity results.…”
Section: Discussionsupporting
confidence: 92%
“…Functional deficits of the ventral attentional network (including the supramarginal and angular gyri) are well known in ADHD (Helenius et al, 2011;Cortese et al, 2012;McCarthy et al, 2013;McLeod et al, 2014) and right-ward hyperactivation of the angular gyrus (Cortese et al, 2012) and a left-ward hypoactivation of the ventral attention system (McCarthy et al, 2013) were previously observed in ADHD adults and could be in line with our connectivity results.…”
Section: Discussionsupporting
confidence: 92%
“…The field has produced inconsistent results in this regard. While most studies have reported reduced DMN connectivity [37,38,44,62], hyperconnectivity has also been observed [40,41] (and one study found hyperconnectivity for some regions and hypoconnectivity for others within the DMN [65]. These inconsistencies may be due to differences between studies in analysis techniques used or sample characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…In the current paper we provide the first test of this hypothesis by exploring the intrinsic organization of DMN, DAN, VAN and SN and their interactions in adults with ADHD by evaluating patterns of BOLD signal correlations measured during rest [32,35,36]. Prior resting state studies have found reduced connectivity in ADHD between DMN regions [37][38][39]; for opposite findings see Tian et al, [40], McCarthy 5 et al, [41], as well as altered organisation of DAN and VAN [21,41,42]. However, no study has directly explored connectivity within and between the DMN, DAN, VAN and SN in ADHD.…”
Section: Introductionmentioning
confidence: 89%
“…Correlation maps were produced by extracting the BOLD time course from a seed region (10-mm sphere each), and then computing the correlation coefficient between that time course and the time course from all other brain voxels. Based on data from previous connectivity studies (Fox et al, 2006;Sheline et al, 2010;McCarthy et al, 2013), the left and right subgenual anterior cingulate cortex (ACC; 7x ¼ 10, y¼ 35, z ¼2) was extracted as the seed region of interest from the affective network that was modulated between ToM trials and NULL events; and the left and right precuneus ( 7x ¼7, y¼ À60, z ¼ 21) as the seed region of interest in the DMN during NULL events. Thus, the DMN was modulated during rest (NULL events) and the ToM network was modulated by functional variation in ToM and NULL events.…”
Section: Functional Coupling Analysismentioning
confidence: 99%
“…As a result, it has been identified as an important region in the study of the psychopathology of various disorders typified by emotion dysregulation (Stevens et al, 2011). Furthermore, the ACC is known as a good seed region to investigate the affective network (Sheline et al, 2010;McCarthy et al, 2013). The second part of the study addressed the gap in research on the DMN in BPD patients by mapping the functional connectivity corresponding to the precuneus seed region within the DMN in a sample of BPD patients compared with healthy controls during resting state.…”
Section: Introductionmentioning
confidence: 99%